HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN IBU HAMIL MENGHADAPI PROSES PERSALINAN DI WILAYAH KERJA PUSKESMAS SIKAPAK KOTA PARIAMAN - Miftakhul Zanah; Miftakhul Zanah (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2021)
One of the causes of MMR in Indonesia is the lack of attention from the family, especially the husband's participation in the process during pregnancy. Even though the husband's role is very important to help calm a wife's physical and psychological condition. The result of the lack of attention and support from the husband makes the mother feel afraid, anxious and worried in facing childbirth. The impact of anxiety experienced by mothers during childbirth is that the mother will become tired and lose strength so that it can interfere with the labor process. This research was conducted from 4 September to 23 September in the Sikapak Community Health Center, with 30 respondents who were taken using purposive sampling technique. Respondents who are willing to be the research sample are then asked to complete the questionnaire. Data analysis used the univariate test to determine the frequency distribution of respondents and bivariate analysis using the Chi-square test to see how the relationship between variables. After the statistical test was carried out, it was found that there was a significant relationship between family support and anxiety of pregnant women in facing the delivery process in the work area of Puskesmas Sikapak, Kec. Pariaman Utara Kota Pariaman in 2018 (p value = 0.011 <0.05). The conclusion of this study is that there is a significant relationship between family support and anxiety of pregnant women in facing childbirth (p value = 0.011> 0.05).